2019
DOI: 10.1111/jog.14042
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of the Edinburgh Postnatal Depression Scale as screening for post‐partum depression in Iwate Prefecture, Japan

Abstract: Aim: Although the Edinburgh Postnatal Depression Scale (EPDS) is widely used for screening for postpartum depression (PPD), screening time point and cut-off value in the current medical environment are not sufficiently examined. In this study, we examined appropriate timing and cut-off value of EPDS for the diagnostic criteria of Diagnostic and Statistical Manual of Mental Disorders Fifth Edition. Methods: This study was a prospective cohort study of women who delivered at the Iwate Medical University Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…The EPDS-S and FREQ-S both showed that non-pregnant women scored higher than pregnant women overall and pregnant women in their 20s, indicating that early pregnancy is a relatively less stressful situation than a regular life for female students in their 20s. However, it was clearly lower than the previously reported EPDS positivity rate in pregnant women [ 2 , 23 , 24 ]. The reason for the low positivity rate in this study might be that it was conducted in a general obstetrics and gynecology department.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The EPDS-S and FREQ-S both showed that non-pregnant women scored higher than pregnant women overall and pregnant women in their 20s, indicating that early pregnancy is a relatively less stressful situation than a regular life for female students in their 20s. However, it was clearly lower than the previously reported EPDS positivity rate in pregnant women [ 2 , 23 , 24 ]. The reason for the low positivity rate in this study might be that it was conducted in a general obstetrics and gynecology department.…”
Section: Discussioncontrasting
confidence: 78%
“…According to the EPDS manual, 2nd edition [ 22 ], scores of 10 or more indicate high depressive symptoms, and a cutoff value of 10 is recommended for research use. The cutoff value for the Japanese version of the EPDS has been recommended by the Japanese Society of Obstetrics and Gynecology to be 9 points for postpartum pregnancy and 13 points for pregnancy, based on results of the studies by Usuda and Okano [ 2 , 23 , 24 ]. There is heterogeneity in the reported sensitivity and specificity of the cutoff scores among studies, which may be due to various factors, such as study methodology, language, or diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the risk-of-bias assessment of the methods used to evaluate psychometric measurement properties of PROMs in individual studies are provided in eTable 1 in the Supplement. Thirty-three studies 25,26,29,30,[32][33][34][35][36][37][38]40,[42][43][44][45][46][47][48][49][50]52,[54][55][56][57][58][59][60][62][63][64]66 were graded as very good for methods, 11 studies 24,26-28,31,48,51,53,60,61,65 as adequate, and 2 studies 39,41 as doubtful (eTable 1 in the Supplement). were frequently downgraded for study design (convenience sampling predisposing to selection bias), 24,[27][28][29][30][31][32]35,36,49,51,53,54,…”
Section: Risk Of Biasmentioning
confidence: 99%
“…were frequently downgraded for study design (convenience sampling predisposing to selection bias), 24,[27][28][29][30][31][32]35,36,49,51,53,54,60 inadequate response rate (<60%), 37,[44][45][46]55,66 or low numbers of study patients (<100), resulting in imprecision. 31,33,35,36,57,58,60…”
Section: Risk Of Biasmentioning
confidence: 99%
“…According to a recent report, 60% of mothers who committed suicide in the first year of childbirth in the 23 wards of Tokyo had mental illness, and postpartum depression (PPD) was the most common (33%) 1 . The incidence of PPD has been reported to be 10–15% 2 in developed countries and we reported an incidence of 11.3% in Japan in a previous study 3 . Depressive symptoms have been reported in more than 25% of perinatal women 2 , 4 .…”
Section: Introductionmentioning
confidence: 46%